Pyroelectric arrays using ceramics and thin films integrated radiation collectors: design fabrication and testing - Whatmore, Roger W.; Landi, Spartaco; Shaw, Christopher P.; Kirby, Paul B. (Taylor and Francis, 2005)
Pyroelectric infra-red detectors have been of-interest for many years because of their wide wavelength response, good sensitivity and lack of need for cooling. Arrays of such detectors, comprising a pyroelectric material interfaced to an application specific integrated circuit for signal amplification and read out, provide an attractive solution to the problem of collecting spatial information on the IR distribution in a scene. Sol gel deposition provides an excellent technique for the growth of ferroelectric thin films and Mn-doped PZT30/70 films can be grown at 560°C with FD = 3.85 × 10-5 Pa-1/2. A new concept is presented here: the use of arrays of thin film pyroelectric detector elements with integrated radiation collectors designed to enhance the intensity of the radiation falling on the element. Two collector designs are presented, one based on the use of wet-chemically-etched pyramidal cavities, the second based on the Compound Parabolic Concentrator (CPC). Approximations to truncated CPC structures were SF6-dry-etched into a silicon wafer, upon which had been defined pyroelectric IR sensors with low thermal conductance (spiral leg structure) fabricated in a high sensitivity PZT thin film. First experimental assessment of the performance of these structures is presented.
Keywords: Pyroelectrics; IR detector arrays; MEMS; dry etching